E‐cadherin is downregulated in benign prostatic hyperplasia and required for tight junction formation and permeability barrier in the prostatic epithelial cell monolayer. Issue 11 (18th June 2019) - Li, Feng; Pascal, Laura E.; Stolz, Donna B.; Wang, Ke; Zhou, Yibin; Chen, Wei; Xu, Yadong; Chen, Yule; Dhir, Rajiv; Parwani, Anil V.; Nelson, Joel B.; DeFranco, Donald B.; et al.
Abstract: Background: We previously reported the presence of prostate‐specific antigen (PSA) in the stromal compartment of benign prostatic hyperplasia (BPH). Since PSA is expressed exclusively by prostatic luminal epithelial cells, PSA in the BPH stroma suggests increased tissue permeability and the compromise of epithelial barrier integrity. E‐cadherin, an important adherens junction component and tight junction regulator, is known to exhibit downregulation in BPH. These observations suggest that the prostate epithelial barrier is disrupted in BPH and E‐cadherin downregulation may increase epithelial barrier permeability. Methods: The ultra‐structure of cellular junctions in BPH specimens was observed using transmission electron microscopy (TEM) and E‐cadherin immunostaining analysis was performed on BPH and normal adjacent specimens from BPH patients. In vitro cell line studies using benign prostatic epithelial cell lines were performed to determine the impact of small interfering RNA knockdown of E‐cadherin on transepithelial electrical resistance and diffusion of fluorescein isothiocyanate (FITC)‐dextran in transwell assays. Results: The number of kiss points in tight junctions was reduced in BPH epithelial cells as compared with the normal adjacent prostate. Immunostaining confirmed E‐cadherin downregulation and revealed a discontinuous E‐cadherin staining pattern in BPH specimens. E‐cadherin knockdown increased monolayer permeability and disrupted tight junction formation without affecting cell density. Conclusions: Our results indicate that tight junctions are compromised in BPH and loss of E‐cadherin is potentially an important underlying mechanism, suggesting targeting E‐cadherin loss could be a potential approach to prevent or treat BPH.